Studies on the bacterial species associated with digestive disturbance in pigs - Balakrishna Pillai K P (Department of Microbiology, College of veterinary and animal Sciences, 1975)
Prior to this investigation, limited studies conducted in the department of Bacteriology, College of Veterinary and Animal Sciences, Mannuthy, have revealed the association of pathogenic strains of E. coli and Salmonella with enteric disorders of pigs. Therefore, a detailed study of the incidence and magnitude of prevalence of those pathogens was carried out. A total of 274 specimens collected from sick as well as dead animals were examined. Faecal materials collected from living as well as dead animals, mesentric lymphnode, spleen, liver, lungs and heart blood formed the materials for isolation studies. Both enrichment and selective media like selenite and tetrathionate broth, D. H. S. broth and D.H.S. agar, modified MacConkey medium 1 & 11, and composite medium 1 & 11 were employed for isolation of pathogens. A total of 75 strains of E. coli and 24 strains of Salmonella were isolated and studied. Most of the isolations were made from piglings ages 3 – 8 weeks. Out of 75 strains of E. coli only 5 strains were found pathogenic based on various tests like haemolysin, necrotoxin and enterotoxin production and pathogenicity to mice. These isolates belonged to serogroup 05, 017 and 039. Salmonella strains belonged to two serotypes, S. weltevreden and S. typhimurium var coCopenhagen The identity of the isolates were confirmed biochemically and serologically. Pathogenicity studies conducted with two strains of Salmonella weltevreden and Salmonella typhimurium Var Copenhagen have revealed that they were pathogenic to laboratory animals like mice, guinea pigs and rabbits. It has also been observed that these serotypes could produce enteric form of the disease in primary hosts. Invitro drugsensitivity studies were carried out to determine the effectiveness of antibiotic to gastrointestinal disorders the effectiveness of antibiotic to gastrointestinal disorders caused by these species. It has been observed that all E. coli and Salmonella strains tested were sensitive to chloramphenicol. However multiple resistance was observed to penicillin, streptomycin, tetracycline, erythromycin and nitrofurantoin. The significance, possible role of infection by these species and their drug sensitivity reactions are discussed.